Enacyloxin IIa, an inhibitor of protein biosynthesis that acts on elongation factor Tu and the ribosome. - Cetin, R (1996)
This work analyzes the action of enacyloxin Ila, an inhibitor of bacterial protein biosynthesis. Enacyloxin IIa [IC50 on poly(Phe) synthesis approximately 70 nM] is shown to affect the interaction between elongation factor (EF) Tu and GTP or GDP; in particular, the dissociation of EF-Tu-GTP is strongly retarded, causing the Kd of EF- Tu-GTP to decrease from 500 to 0.7 nM. In its presence, the migration velocity of both GTP- and GDP-bound EF-Tu on native PAGE is increased. The stimulation of EF-Tu-GDP dissociation by EF-Ts is inhibited. EF- Tu-GTP can still form a stable complex with aminoacyl-tRNA (aa-tRNA), but it no longer protects aa-tRNA against spontaneous deacylation, showing that the EF-Tu-GTP orientation with respect to the 3' end of aa-tRNA is modified. However, the EF-Tu-dependent binding of aa-tRNA to the ribosomal A-site is impaired only slightly by the antibiotic and the activity of the peptidyl-transferase center, as determined by puromycin reactivity, is not affected. In contrast, the C-terminal incorporation of Phe into poly(Phe)-tRNA bound to the P-site is inhibited, an effect that is observed if Phe-tRNA is bound to the A-site nonenzymatically as well. Thus, enacyloxin IIa can affect both EF-Tu and the ribosomal A-site directly, inducing an anomalous positioning of aa-tRNA, that inhibits the incorporation of the amino acid into the polypeptide chain. Therefore, it is the first antibiotic found to have a dual specificity targeted to EF-Tu and the ribosome.